Neuronal and Glial Responses to Polyamines in the Ischemic Brain - Takano, Katsura; Ogura, Masato; Nakamura, Yoichi; Yoneda, Yukio (Current Neurovascular Research, 2005)
The polyamines, putrescine, spermidine and spermine are present in most living cells, with the essentiality for normal cell function, cellular growth and differentiation. In the mammalian brain, polyamines are also present at relatively high concentrations with different regional distribution profiles. Cerebral ischemia is a leading cause of disability and mortality in humans, and believed to yield a cascade of cytotoxic molecules responsible for the death of viable cells in the brain. Polyamines have been implicated in the pathogenesis of ischemic brain damage. For example, polyamine biosynthesis is increased after the onset of cerebral ischemia through an induction of ornithine decarboxylase, a key enzyme in the polyamine biosynthetic pathway. The administration of a drug that inhibits ornithine decarboxylase activity prevents the development of ischemic brain damage, suggesting a critical role of the accumulation of polyamines in the ischemic brain in the pathogenesis of stroke. Both spermine and spermidine are linked to the development of glutamatemediated neurotoxicity, for they can bind to the N-methyl-D-aspartate (NMDA)-sensitive subtype of glutamate receptors to potentiate cellular responses to glutamate. Moreover, polyamines are metabolized by polyamine oxidases after acetylation to produce different cytotoxic aldehydes and reactive oxygen species such as hydrogen peroxide, which possibly damage proteins, DNA and lipids. Polyamines have been extensively studied in the ischemic brain, particularly with respect to neuronal responses such as NMDA receptor-mediated excitotoxicity. However, little is known about glial responses to polyamines in the ischemic brain to date. In this review, we would summarize previous studies related to neuronal and glial responses to polyamines in the ischemic brain.
Keywords: polyamines